Dziedzictwo kulinarne w kontekście europejskiego ruchu turystycznego - Świtała-Trybek, Dorota (Studia Etnologiczne i Antropologiczne, 2014)
Traditional cuisine is very important for tourism. It influences the attractiveness of particular countries, regions, places; it enables their economic development. The reference to the cultural heritage has many various forms (routes, festivals, competitions, culinary workshops). On the map of Europe there are „old” culinary routes, with their long history; they are recognisable and described in guide books. There are also new ones, a product of the activity of local communities, the implementation of EU programmes etc.